EVALUASI KELEMBAGAAN PERANGKAT DAERAH KABUPATEN KUNINGAN - Jona Bungaran Basuki Sinaga (Program Studi Manajemen Keamanan dan Keselamatan Publik IPDN, 2020)
This study evaluates the organizations, identifies the potential primary functions, and redesigns the institution of Kuningan Regency Government. The research design is qualitative, and the discussion is carried out by combining theoretical and legal analyses. The results present that the structural arrangement and task distribution within the organizations do not result in a harmony to achieve the development mission. The institutional design should refer to the regional vision and mission emphasizing on three primary functions: agriculture; tourism; environment. For this reason, it should pay attention to the strengthening and harmonizing the offices of agriculture, tourism, and environment, as well as those responsible in delivering education, health, public works and spatial planning, public housing and settlement, public order and social functions. Keywords: Restructurization; Institutions; Local Department